LEARNING METHOD, FACILITIES AND INFRASTRUCTURE, AND LEARNING RESOURCES IN BASIC NETWORKING FOR VOCATIONAL SCHOOL - Bian Dwi Pamungkas (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2017)
This study aims to examine the contribution of learning methods on learning output, the contribution of facilities and infrastructure on output learning, the contribution of learning resources on learning output, and the contribution of learning methods, the facilities and infrastructure, and learning resources on learning output. The research design is descriptive causative, using a goal-oriented assessment approach in which the assessment focuses on assessing the achievement of a goal. The population in this study are teachers and students involved in English for Vocational School subject, namely the Class X of Multimedia and TKJ expertise. The samples in this study are teachers and students of Class X in Multimedia and TKJ expertise at SMK Negeri 1 Pogalan. The results shows that the contribution of learning methods on learning output is 31.57%, the contribution of facilities and infrastructure to the learning output is 19.824%, and the contribution of learning resources to the learning output is 16.112%. The contribution of learning methods, facilities and infrastructure, and learning resources to the learning output is 67.506%.